A critical analysis of the advantages brought by blockchain technology to the global economy. (17th June 2019) - Porras-Gonzalez, Eva Raquel; Martín-Martín, José María; Guaita-Martínez, José Manuel
The blockchain distributed ledger technology offers a secure, transparent, verifiable, democratic, decentralised, efficient, and tamper-resistant way to record and transfer data. Now much of the discussion revolves around the attributes that determine its many potential applications as this technology is expected to help transform sectors that are hampered by inefficiencies as well as facilitate the appearance of new business models based on distributed markets and technology. Given this technological revolution has already started, the core objectives of this article are to acquaint the reader with the technology and with the current and latent applications of this innovation while recognising its potential worldwide economic impact. To accomplish these goals we review the literature encompassing both academic and professional works that refer to the characteristics and properties of the blockchain, its many existent and plausible applications, and the reasons for its anticipated global economic repercussions.